Ang pilya [videorecording] - Cultural Center of the Philippines ([Manila] The Center, 1988)
A ballet presentation of the customs and traditions of the Filipinos.
VHS.
Keywords: Ballet -- Philippines; Ang pilya (choreographic work).; Ang pilya (ballet); THEATER ARTS; HUMANITIES